Inevitable relative age effects in different stages of the selection process among male and female youth soccer players - Lagestad, P.; Steen, I.; Dalen, T. (Sports, 2018)
The relative age effect (RAE) in the selection of young soccer players is a well-known phenomenon. The purpose of this study was to examine the relative age effect existing despite strategies that have been implemented to avoid its presence in the selection process. We also aimed to investigate the RAE during the three different selection stages for B13, B14 (boys), and G13, G14 (girls), and gender differences in the RAE. This was achieved by collecting data from everyone who played soccer in Troendelag, and data that would illuminate the RAE during the three stages of selection for the regional teams of the 2015/2016 season. Mann-Whitney U-tests and Chi-square tests were used as statistical methods. The main finding of this study is that, despite the intention to reduce RAE in the selection process according to the criterion that at least 40% of the players should be born in the second half of the year, both the early-born boys and girls are more likely to be selected. The results also show that the RAE occurs gradually, and the longer the players are in the selection process the more prominent it is. This study highlights the importance of being aware of the RAE when selecting young players.